2000
DOI: 10.1002/(sici)1521-4109(200002)12:2<134::aid-elan134>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Selective Determination of Vitamin B2 at Electrochemically Activated Glassy Carbon Electrode

Abstract: Electrochemically activated glassy carbon electrodes were applied to the preconcentration and electroanalysis of Vitamin B 2 (VB 2 ) in multivitamin preparation. Voltammetric peak currents resulting from VB 2 species adsorbed on activated electrodes showed linear response for VB 2 concentrations in the range between 0.1 and 3.0 mM with a large slope of 12.2 A M 71 and a correlation coef®cient of 0.996. The reproducibility of the voltammetric measurements was usually less than 7 % RSD for ®ve replicate measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
(12 reference statements)
0
9
0
1
Order By: Relevance
“…24,25 In our previous studies, cationic copper species and small organic molecules, such as DHB, were found to incorporate onto the glassy carbon electrodes obtained by electrochemical pretreatment in sulfuric acid. [21][22][23] Quasireversible redox behaviors were observed for the background voltammetric response of the activated electrodes. [21][22][23] Copper cations, chloride anions, DHB and NADH have different molecular sizes and charges, and should be suitable molecular probes to investigate the effects of surface structures of the glassy carbon obtained by different pretreatment methods on their electrochemical behaviors.…”
Section: Resultsmentioning
confidence: 97%
“…24,25 In our previous studies, cationic copper species and small organic molecules, such as DHB, were found to incorporate onto the glassy carbon electrodes obtained by electrochemical pretreatment in sulfuric acid. [21][22][23] Quasireversible redox behaviors were observed for the background voltammetric response of the activated electrodes. [21][22][23] Copper cations, chloride anions, DHB and NADH have different molecular sizes and charges, and should be suitable molecular probes to investigate the effects of surface structures of the glassy carbon obtained by different pretreatment methods on their electrochemical behaviors.…”
Section: Resultsmentioning
confidence: 97%
“…It has been proved that the surface of electrode could generate oxygen–containing functional groups (such as carboxyl, carbonyl, hydroxyl, etc.) after sulfuric acid activation which is negatively charged 24 25 26 . So the positively charged surface of the GNRs can adsorb on the negatively charged surface of GCE after activation through electrostatic adsorption, and do not need to use nafion or chitosan as adhesion agent which has poor conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16] Electrochemically activated GCE usually gives reproducible surface, improved electron transfer and specific adsorption behaviors. [17][18][19][20] Although the electrochemically activated GCE has been exploited in electrochemical applications, its potential for simultaneous determination of HQ and CC has been rarely reported. More recently, Ahammad et al demonstrated the use of polarized GCE for simultaneous determination of HQ and CC.…”
Section: Introductionmentioning
confidence: 99%